Pentecostal/Charismatic Churches and the Provision of Social Services in Ghana - Benyah, Francis (Transformation, 2021)
The provision of social services by Pentecostal/Charismatic churches in Ghana is discussed in this article. Focusing on four selected Pentecostal/Charismatic churches in Ghana, it is argued that Pentecostal/Charismatic churches are not only concerned with the proclamation of the gospel of Jesus Christ but are also actively engaged in the provision of social and welfare services aimed at transforming the lives of their constituents. This development, in the author’s view, points to a paradigm shift from the well-known otherworldly nature of the Pentecostal/Charismatic movements and projects a rather new movement whose growing social sensitivity has implications for national development.